Effectiveness of knowledge transfer among employees in JARING / Noor Latifa Ismail ... [et al.] - Ismail, Noor Latifa; Yaacob, Raja Abdullah; Azli Bunawan, Ap; Salleh, Mohd Idzwan (Faculty of Information Management, 2013)
This study surveyed the effectiveness of knowledge transfer practice in an organization. Knowledge transfer is a major strategy for contemporary organizational management and the impact of the major factors that influence the rate of organizational knowledge transfer is fairly unknown. This study aims to investigate the influence of organizational factors (IT, learning strategy, trust culture, and flexible structure and design) on knowledge transfer using a framework derived and adapted from the literature. A study was conducted amongst 200 employees in JARING and from the questionnaires that were distributed, 170 responded. The findings revealed that the most significant factor that impacted knowledge transfer in a particular organization is learning strategy. The findings can be used by the organization in order to manage their resource allocation to further optimize their organizational performance.